HUBUNGAN TINGKAT PENGETAHUAN PERAWAT TENTANG KESELAMATAN PASIEN DENGAN INSIDEN KESELAMATAN PASIEN DI RS AMINAH TAHUN 2021 - Imaniar, Imaniar; Banjarnahor, Seriga (Indonesian Trust Health Journal, 2021)
Knowledge is something related to the learning process. Patient safety is a system in which the hospital makes patient care safer. A Patient Safety Incident (IKP) is an event or situation that could potentially or result in injury to a patient that should not have occurred. This study aims to determine the relationship between the level of knowledge of nurses about patient safety with patient safety incidents at Aminah Hospital in 2021. This study is a descriptive quantitative correlation study with a cross sectional approach. The test carried out in this study is the chi square test. The population studied were nurses who were inpatient and outpatient at Aminah Hospital, samples taken were 55 people who were taken by means of probability sampling. The data were processed using univariate and bivariate analysis. From the chi square test results obtained p value = 0.000 (p <0.05). From the results of the research that has been done, it can be concluded that there is a relationship between nurses' knowledge of patient safety and patient safety incidents at Aminah Hospital. From the results of this study, it is expected that hospitals can improve the quality of nursing services, especially for health workers, especially nurses who act as nursing care providers. The quality of service is supported by the performance of nurses based on good knowledge. Abstrak Pengetahuan merupakan sesuatu yang berkaitan dengan proses pembelajaran. Keselamatan pasien merupakan suatu sistem dimana rumah sakit membuat asuhan pasien lebih aman. Insiden Keselamatan Pasien (IKP) merupakan kejadian atau situasi yang dapat berpotensi atau mengakibatkan cedera pada pasien yang seharusnya tidak terjadi. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pengetahuan perawat tentang keselamatan pasien dengan insiden keselamatan pasien di RS Aminah tahun 2021. Penelitian ini merupakan penelitian deskriptif korelasi metode kuantitatif dengan pendekatan penelitian cross sectional. Uji yang dilakukan pada penelitian ini adalah uji chi square. Populasi yang diteliti adalah perawat pelaksana di rawat inap dan rawat jalan RS Aminah, sampel yang diambil 55 orang yang diambil dengan cara probability sampling. Data diolah menggunakan analisa univariat dan bivariat. Dari hasil uji chi square di dapatkan p value = 0,000 (p < 0,05). Dari hasil penelitian yang telah dilakukan dapat disimpulkan bahwa adanya hubungan antara pengetahuan perawat tentang keselamatan pasien dengan insiden keselamatan pasien di RS Aminah. Diharapkan rumah sakit dapat meningkatkan kualitas pelayanan keperawatan terutama bagi tenaga kesehatan yang berperan sebagai pemberi asuhan keperawatan. Kualitas pelayanan didukung oleh kinerja perawat yang didasari oleh pengetahuan yang baik.